"I Always Knew I was a Little Girly": The gendering of skills in management training. Issue 5 (November 2019) - Blithe, Sarah Jane
This article examines the ways in which popular management texts organize individual behavior in gendered ways at work. Taking the 'Strengths' program as an example of a popular management text that shapes action, the study finds that even though the text itself makes no explicit reference to gender, it (re)produces and encourages gendered behavior and perpetuates stereotypes about gender and skill. Based on textual analysis, auto-ethnographic accounts, and critical reflection of strengths-based corporate training sessions, the study concludes with a discussion about the ways that organizational texts are consumed through a gendered lens.